2021
DOI: 10.3389/fnut.2021.715528
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Analysis of Volatile and Non-volatile Compounds in Vitis Vinifera Berries (cv. Chardonnay) and Spontaneous Bud Mutation

Abstract: A novel clonal variety of Vitis vinifera was identified from “Chardonnay” using inter-simple sequence repeat (ISSR) markers and called “bud mutation. ” The metabolomic profiles in Chardonnay and bud mutation berries indicated essential differences in the expression of key genes in the pathways of 2-C-methyl-D-erythritol-4-phosphate (MEP) and lipoxygenase-hydroperoxide lyase (LOX-HPL). Bud mutation fruits also matured 10 days earlier than Chardonnay and have higher carotenoid, sugar, and acidic compound content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
4
1
Order By: Relevance
“…That this variation produces unexpected results is worthy of further study. Previous studies in orange and grape found that the mutants had significantly higher TSS/TA values compared to the wild type, indicating that they would ripen slightly earlier than the parental plants [32,33]. Contrary to this, our results have found that MT fruit TSS/TA was significantly lower, presumably maturing later in MT than WT.…”
Section: Natural Variation and Rootstocks Effect The General Morpholo...contrasting
confidence: 99%
“…That this variation produces unexpected results is worthy of further study. Previous studies in orange and grape found that the mutants had significantly higher TSS/TA values compared to the wild type, indicating that they would ripen slightly earlier than the parental plants [32,33]. Contrary to this, our results have found that MT fruit TSS/TA was significantly lower, presumably maturing later in MT than WT.…”
Section: Natural Variation and Rootstocks Effect The General Morpholo...contrasting
confidence: 99%
“…2-phenylethyl acetate is a very valuable flavor compound that provides a stronger fruity character in wine ( Viana et al, 2009 ). Benzoic acid methyl ester is a food-grade oral favor additive ( Zheng et al, 2021 ). Most Maillard reaction products can offer a sweet, nutty, or popcorn-like flavor ( Hinneh et al, 2018 ), in which 1H-Pyrrole-2,5-dione, 3-ethyl-4-methyl- has been reported as a flavor marker in dark tea (strongly associated with an aged fragrance) and 2,5-dimethylpyrazine offers a cocoa flavor ( Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ScB is an important alternative when it comes to reducing sulfur dioxide rates, in addition to requiring lower recurrence doses. According to Togores, 16 yeasts form or consume sulfites during alcoholic fermentation. The formation varies between 10 and 30 mg L −1 , whereas consumption can be up to 100 mg L −1 , and the present work results (Table 1) show clearly that different strains of S. cerevisiae imply changes in the parameter.…”
Section: Physicochemical Analyses Of Must End Of Fermentation and Bas...mentioning
confidence: 99%